Re: All the M&E design immediately to be reviewed by the Transsolar - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the reply on completing all the M&E design immediately to be reviewed by the Transsolar for BRACU new campus project.